Optimalisasi Sim Online Sebagai Strategi untuk Mewujudkan Pelayanan Prima pada Kantor Satpas Jember - Agnes Juwita* (Universitas Airlangga, 2018)
Service reform in Indonesia has links with decentralization. The aim of implementing service reforms throughout Indonesia is to improve service quality so as to create public trust in the government. The problem of SIM services is one of the internal problems in terms of service to the community. Therefore, SIM services must be excellent in accordance with the standards of the technological era that is growing at this time. Seeing this development, the Chief of the Republic of Indonesia National Police (Kapolri) General Police M. Tito Karnavian launched a future program for the National Police which is called the Promoter program. Promoter main policy, focused on 3 (three) main substances, namely Improved Performance, Improved Culture and Media Management. SIM Services in the Administrative Unit of the SIM Administration (SATPAS) of the Jember Police Department itself, based on the pre-survey conducted by the service researchers in making and extending the SIM, were still inadequate or had not yet achieved excellent service, especially regarding Polri's human resources at Samsat Jember. hampered by a good understanding of e-policing policies. In connection with these problems, the Jember Police SIM Administration Unit (SATPAS) conducted an opinion poll (survey questionnaire) during January to April 2015. The online service system is a form of government policy based on Presidential Instruction (Inpres) No. 3 of 20043 about national policies and strategies for the development ofe-government. The basic reason for the emergence of online services is to eliminate the practice of brokering and to reduce criminal acts of corruption within the National Police. Then also to increase community satisfaction inthe realization to become administrative citizenship, which is related to the ownership of a Driving License (SIM). Seeing this reality, it becomes interesting to conduct research on the problem with the title “Optimalisasi SIM Online Sebagai Strategi untuk Mewujudkan Pelayanan Prima pada Kantor Satpas Jember ”.